2003
DOI: 10.1111/j.1348-0421.2003.tb03447.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Helicobacter pylori Infection in Children and Clonality of Taiwan Strains

Abstract: The spiral shaped bacterium, Helicobacter pylori, is now regarded as the major cause of stomach diseases such as acute gastritis, gastric and duodenal ulcers, gastric lymphoma, and gastric adenocarcinoma (1,18). Many surveys have revealed that the number of the infected is low in the younger age and increases as a function of age, reaching a plateau at old age. The surveys also showed that the infection might be related to the state of hygiene: the poorer the hygiene, the higher the infection rate (6,9,11,20).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…We think that this is may be an artifact of studying only 6‐ and 9‐year‐olds rather than a wider age range. Several epidemiological reports have shown that the rate of H. pylori infection increases significantly with age, with more than 80% of children being infected by the age of 10 years 10–15 . Although the chronic diseases linked to H. pylori are predominantly of adult onset, this bacterium often infects young children, but infection often remains asymptomatic and so it is difficult to obtain precise estimates of the age of acquisition 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…We think that this is may be an artifact of studying only 6‐ and 9‐year‐olds rather than a wider age range. Several epidemiological reports have shown that the rate of H. pylori infection increases significantly with age, with more than 80% of children being infected by the age of 10 years 10–15 . Although the chronic diseases linked to H. pylori are predominantly of adult onset, this bacterium often infects young children, but infection often remains asymptomatic and so it is difficult to obtain precise estimates of the age of acquisition 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…As major pathogen to cause gastric and duodenal ulcer and possibly gastric cancer, H. pylori can infect repeatedly more than 90% of adults (Chu et al, 2003). In this study, we established a procedure to produce the anti-H. pylori IgY through the eggs of White Leghorn hens.…”
Section: Resultsmentioning
confidence: 99%
“…Helicobacter pylori infection is frequently observed in adults worldwide and causes gastric and duodenal ulcers, gastric lymphoma, and possibly gastric carcinomas (Shin et al, 2002;Chu et al, 2003). Neutralization of highly acidic environment by secreted urease leads to Helicobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…A mammalian expression vector pcDNA3.1(-) encoding 717 bp H. pylori antigen Urease alpha (GenBank: AF373569.1) [19] was synthesised by Genscript (Piscataway, NJ, USA). The 5782 bp construct was amplified in Escherichia coli strain DH5α and purified using the QIAprep Spin Miniprep Kit (Qiagen, Germantown, MD, USA) and stored at −20 • C until use.…”
Section: Synthesis Of Mammalian Plasmid Vaccine Pcdna31-ureamentioning
confidence: 99%